Evaluation of Mandibular Third Molar Extractions Performed By Intra Alveolar Method as Opposed to Transalveolar Method - Aniruddh Menon1 , Balakrishna.R.N2 , Jayanth Kumar Vadivel3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the present study was to retrospectively analyse the prevalence of intra-alveolar and transalveolar extraction of mandibular third molars in patients at Saveetha Dental college. Retrospective dataof 1747 patients was obtained and segregated. The inclusion criteria included 18-90 years are group,underwent extraction and visited between June 2019 to April 2020. Once the data was obtained it wasstatistically analyzed using SPSS by IBM version 20. The most commonly used method of extraction wasthe conventional technique (90.8%) comprising the majority whereas the trans alveolar method comprised(9.2%). A high association and significance was noticed between the age of the patient and type of extractionperformed( P= 0.000)Extraction being one of the most common dental procedures that is being done, it isimportant to approach the same with the adequate and appropriate technique to prevent further complicationsas a result of the procedure